Advances in Treatment of Hepatitis C and B - Allam, Naglaa (IntechOpen, 2017)
As in many areas of medicine, treatment of viral hepatitis has seen an acceleration of change driven by new therapies and evolving technology. Thanks to the direct-acting antiviral agents (DAAs), the era of HCV eradication and cure has begun. As regards to hepatitis B therapy, potent antiviral drugs for suppression of viral replication are available, new research activities to enhance eradication are visible, and these may influence clinical practice in the coming years. This book covers the latest advances in hepatitis C and hepatitis B therapeutics as well as the emerging and investigational treatment strategies. "Advances in Treatment of Hepatitis C and Hepatitis B" book is an up-to-date source of information for physicians, residents, and advanced medical students seeking a broader understanding of treatment of viral hepatitis. The authors of the chapters come from many eminent centers around the world and are experts in their respective fields.